TRANSLINGUAL PRACTICES IN ESL/EFL CLASSROOMS IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Translingual refers to the practice of using multiple languages flexibly in communication, rather than strictly separating them. It allows speakers to draw on different linguistic resources to express ideas more effectively. In ESL/EFL classrooms, translingual practices help learners use their first language (L1) alongside the second language (L2) to enhance understanding and participation. This approach recognizes language fluidity and supports more natural language acquisition in multilingual settings. Translingual practices play an essential role in ESL/EFL classrooms, allowing students and teachers to use multiple languages for better communication and learning. Instead of rigid monolingual methods, enabling bilingual students to think critically and articulate their ideas freely in both their first (L1) and second language (L2), improving understanding and participation